Analyzing porous cold storage unit in presence of hybrid nano-powders considering Galerkin method - Hatem Gasmi; Ali Basem; Hussein A.Z. AL-bonsrulah; Saeed A. Asiri; Khaled M. Alfawaz; Mohammed A. Tashkandi; Lioua Kolsi; Ageel F. Alogla; Nidal H. Abu-Hamdeh; Walid Aydi (Case Studies in Thermal Engineering, 2024)
The article presents a comprehensive simulation study on cold storage porous containers, employing the Galerkin method to analyze their thermal behavior. A key focus of the investigation is the incorporation of both radiation and conduction modes within the mathematical model, acknowledging their significant roles in the freezing process. To enhance the freezing rate, hybrid nanoparticles are introduced into H2O, aiming to speed up the solidification. Notably, the study integrates adaptive grid techniques to achieve higher modeling accuracy, with verification processes confirming a high level of agreement between simulation results and experimental data. This research also underscores the potential for improved energy efficiency in cold storage systems, contributing to the sustainability of natural resources by reducing energy consumption and enhancing the overall efficiency of thermal storage systems. Through meticulous examination, the study explores the impacts of various factors on freezing, including the fraction of hybrid nano-powders (ϕ), porosity (γ), and the radiation factor (Rd). Remarkably, the introduction of porous media causes to a substantial increment in the freezing rate, resulting in an improvement of approximately 91.19 %. Moreover, the inclusion of the radiation term in the model significantly reduces the completion time by approximately 30.85 %, underscoring the importance of considering radiation effects in such systems. Additionally, dispersing hybrid nano-powders into the water, results in a decrement in the freezing time around 7.21 %. This approach highlights the significant potential for optimizing energy use in thermal storage applications, thereby promoting the conservation and sustainable management of natural resources.